Produção de sementes do capim-branquiária : efeitos da remoção da forragem do corte de rebaixamento e da adubação nitrogenada - Vendruscolo, Marice Cristine (2014)
Seed production of signalgrass (Brachiaria decumbens Stapf. cv. Basilisk) can be limited by not removing of plant residues after closing cleaning cut and by nitrogen fertilization. This study aimed to assess in signalgrass the effects of removal plant residues after close cleaning cut and N levels on seed yield and its components, and seed quality, in two consecutive growing seasons. The experimental design was a randomized block design with split plot with three replications. Treatments consisted of the removal or not of plant residues after closing cleaning cut, performed in the last weeks of September 2012 and January 2013 (main plot) and nitrogen levels zero, 50, 100 and 150 kg ha-1 (subplot). Practices of forage removal did not significantly affect the apparent seed yield and pure seed yield, as well as any component of seed quality. The forage removal had a significant effect only in the dry matter ha-1 in both growing seasons, and under the number of tillers with panicles in the growing season in the crop second. The interaction was significant for practice of forage removal and nitrogen levels at apparent seed yield and pure seed yield.